Penerapan Teori Belajar Behavioristik Dalam Pembelajaran PAI di SDIT Cahaya Hati Bukittinggi - Rahma Dona; Muhammad Ersyad Anshari; Hidayani Syam (Pusat Riset dan Inovasi Nasional, 2024)
Abstract: Behavioristic theory is important to study in the learning process, because this theory is easy to apply in educational learning in Indonesia. Learning theory is a combination of interconnected principles and explanations of a number of facts and discoveries related to learning events. This research reviews behavioristic theory and its application in learning. The aim of this research is that it can be applied in PAI learning, apart from educating cognitively, psychomotorically, it can also guide students' behavior in a better direction. The method used by the author is descriptive qualitative which attempts to explain the application of behavioristic theory so that it is able to produce changes in behavior towards students. Through this research, the author tries to reveal the application of behavioristic theory in PAI learning at SDIT Cahaya Hati Bukittinggi as well as changes in behavior that occur in students using a behavioristic theory approach. Based on the research results, it was found that the application of behavioristic learning theory to PAI learning was carried out in several stages, namely, stimulus (encouragement for the delivery of material/motivation from the teacher), response (response from students), while reinforcement/reinforcement was carried out by the teacher using the reward method, punishment, and reinforcement.